GROTESQUE GAMES OF LES’ MARTOVYCH - Pihmanets, R. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article reviews the nature, laws of creation and peculiarities of expression of Les Martovych grotesque style, proves its predominance in the creative thinking of the writer.